Clinical and genetic heterogeneity in autosomal dominant cataract - Ionides, A. (1999)
AIMS—To determine the different morphologies of autosomal dominant cataract (ADC), assess the intra- and interfamilial variation in cataract morphology, and undertake a genetic linkage study to identify loci for genes causing ADC and detect the underlying mutation. METHODS—Patients were recruited from the ocular genetic database at Moorfields Eye Hospital. All individuals underwent an eye examination with particular attention to the lens including anterior segment photography where possible. Blood samples were taken for DNA extraction and genetic linkage analysis was carried out using polymorphic microsatellite markers. RESULTS—292 individuals from 16 large pedigrees with ADC were examined, of whom 161 were found to be affected. The cataract phenotypes could all be described as one of the eight following morphologies—anterior polar, posterior polar, nuclear, lamellar, coralliform, blue dot (cerulean), cortical, and pulverulent. The phenotypes varied in severity but the morphology was consistent within each pedigree, except in those affected by the pulverulent cataract, which showed considerable intrafamilial variation. Positive linkage was obtained in five families; in two families linkage was demonstrated to new loci and in three families linkage was demonstrated to previously described loci. In one of the families the underlying mutation was isolated. Exclusion data were obtained on five families. CONCLUSIONS—Although there is considerable clinical heterogeneity in ADC, the phenotype is usually consistent within families. There is extensive genetic heterogeneity and specific cataract phenotypes appear to be associated with mutations at more than one chromosome locus. In cases where the genetic mutation has been identified the molecular biology and clinical phenotype are closely associated.